Epidemiologic Study of Cystic Fibrosis: 25 years of observational research. Issue 5 (12th January 2021) - Konstan, Michael W.; Pasta, David J.; VanDevanter, Donald R.; Wagener, Jeffrey S.; Morgan, Wayne J.; ,
Abstract: The Epidemiologic Study of Cystic Fibrosis (ESCF) was a prospective observational study of over 32, 000 people with cystic fibrosis (CF) from 250 clinical care sites in North America from 1994 to 2005. Begun as a pharmacovigilance study in connection with the approval of dornase alfa in 1993, ESCF was open to all people with CF treated at any participating site in the United States or Canada. In addition to obtaining safety and effectiveness data on dornase alfa, ESCF collected encounter‐based data to characterize the natural history and management of CF with a special focus on lung disease. During the study, 32, 178 patients reported at least one encounter, contributing 869, 136 encounters, 622, 592 pulmonary function tests, 432, 896 cultures, and 118, 563 pulmonary exacerbations treated with intravenous antibiotics. Although ESCF data collection concluded in 2005, through a collaboration with the U.S. Cystic Fibrosis Foundation Patient Registry, additional follow‐up data through 2017 was available for two‐thirds of patients. This allowed for updating of CF genotype and survival information. Fifty‐six peer‐reviewed publications (cited over 3600 times) resulted from this study. In this manuscript we summarize the published ESCF manuscripts in thematic groups with key study findings and brief comments, and speculate on how ESCF findings will inform future data registries and patient care practices.